PENGUASAAN PEMBELAJARAN BAHASA ARAB SISWA KELAS VII TERHADAP PEMBELAJARAN DARING PADA MADRASAH YTSANAWIYAH AL HASANAH SLAHUNG PONOROGO - Sri ana; Samsul Mukani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
: Learning is a teaching activity carried out maximally by a teacher so that the students he teaches certain materials carry out learning activities well. In other words, learning is the effort made by the teacher in creating certain material learning activities that are conducive to achieving goals in the process of learning activities. This study aims to determine (1) the Arabic language mastery ability of the seventh grade students of MTs Al Hsanah Slahung Ponorogo (2) the results of the application of online Arabic learning in class VII MTs Tsanawiyah Al Hasanah Slahung Ponorogo (3) The results of online Arabic learning on mastery Arabic language for seventh grade students of MTs Al Hasanah Slahung Ponorogo. This thesis research uses mixed methods research. With data collection methods in the form of interviews, observations, documentation and questionnaires. The data collected is related to "Arabic Learning Mastery of Grade VII students towards online learning at Mts Al Hasanah Slahung Ponorogo" Using data analysis techniques, data reduction, data presentation. The results of data analysis obtained: 1) Arabic language mastery of class VII Mts Al Hasanah is less than optimal due to the lack of learning support facilities, 2) the application of online Arabic learning at Mts Al Hasanah starts from planning, implementing activities and evaluating, using online lesson plans and social media, 3) The results of the students' online learning of Arabic have greatly changed and the level of students' ability has decreased.